2019
DOI: 10.3390/su11143787
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Public Playgrounds to Motor, Social, and Creative Development and Obesity Reduction in Children

Abstract: The objective of this work was to examine the perceptions of adults responsible for the care of children in their leisure time about the contribution of public playgrounds to motor, social, and creative development and obesity reduction in children, analyzing these perceptions according to sex, age, educational level, and level of involvement in the child's education of the participants. The sample consisted of 1019 adults responsible for the care of children in their leisure time in Albacete (Spain). A valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Families and caregivers of children tend to agree on the positive contribution of public playgrounds to the development of social, motor, cognitive and physical skills [ 61 ]. Taking into account the opinions of local populations will allow for a better understanding and planning of park design, or if necessary, redesign.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Families and caregivers of children tend to agree on the positive contribution of public playgrounds to the development of social, motor, cognitive and physical skills [ 61 ]. Taking into account the opinions of local populations will allow for a better understanding and planning of park design, or if necessary, redesign.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding park designs that favour a greater commitment to more intense PA, the papers reviewed indicate a positive association between access to parks and PA in children and a lower obesity rate [ 61 , 68 , 69 , 71 ], although previous review studies [ 87 ] did not find accessibility a significant factor in park use for PA. The offer of services increases the use of parks and encourages PA [ 62 , 93 ], with this being especially important for girls [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, a total of n=3 articles (Hinkley et al 2018, McCree et al 2018, Omidire et al 2018 were found to have researched outdoor play among children. In addition, there were n=4 studies identified from 2019 (Gil-Madrona et al 2019, Omidvar et al 2019, Sando 2019, Wainwright et al 2019) and 2021 (Almers et al 2021, Fathirezaie et al 2021, Mygind et al 2021, Riazi et al 2021, respectively, from the three databases. Meanwhile, in 2020, a total of n=2 studies (Bay 2020, Rymanowicz et al 2020 were determined to be related to outdoor play among children.…”
Section: Resultsmentioning
confidence: 99%
“…From the accumulated 13 studies, n=5 (Omidire et al 2018, Sando 2019, Bay 2020, Almers et al 2021, Riazi et al 2021 were qualitative, followed by n=4 (McCree et al 2018, Omidvar et al 2019, Wainwright et al 2019, Rymanowicz et al 2020 mixed-method research design. Meanwhile, n=2 studies (Hinkley et al 2018, Gil-Madrona et al 2019) used quantitative as their research design. Besides that, there were also n=1 (Fathirezaie et al 2021) semi-experimental and n=1 (Mygind et al 2021) cross-sectional studies.…”
Section: Research Design For Implementing Outdoor Playmentioning
confidence: 99%